Cell glycosaminoglycans content modulates human voltage‐gated proton channel (HV1) gating. (29th November 2021) - Orts, Diego J. B.; Arcisio‐Miranda, Manoel
Abstract : Voltage‐gated proton channels (HV 1) have been found in many mammalian cells and play a crucial role in the immune system, male fertility, and cancer progression. Glycosaminoglycans play a significant role in various aspects of cell physiology, including the modulation of membrane receptors and ion channel function. We present here evidence that mechanosensitivity of the dimeric HV 1 channel transduce changes on cell membrane fluidity related to the defective biosynthesis of chondroitin sulfate and heparan sulfate in Chinese Hamster Ovary (CHO‐745) cells into a leftward shift in the activation voltage dependence. This effect was accompanied by an increase in the H + current, and an acceleration of the activation kinetics, under symmetrical or asymmetrical pH gradient (ΔpH) conditions. Similar gating alterations were evoked by two naturally occurring HV 1 N‐terminal truncated isoforms expressed in wild‐type CHO‐K1 and CHO‐745 cells. On three different monomeric HV 1 constructs, no alterations in the biophysical parameters were observed. Moreover, we have shown that HV 1 gating can be modulated by manipulating CHO‐K1 cell membrane fluidity. Our results suggest that the defective biosynthesis of chondroitin sulfate and heparan sulfate on CHO‐745 cell increases membrane fluidity and allosterically modulates the coupling between voltage‐ and ΔpH‐sensing through the dimeric HV 1 channel. Abstract : Voltage‐gated proton channel conducts protons out of the cells, being important in cancer progression, male fertility, and neuronal death. We identified that the mechanosensitivity of the dimeric HV 1 channel transduce changes on cell membrane fluidity related to the defective biosynthesis of GAGs in Chinese Hamster Ovary cells into a leftward shift in the activation voltage dependence and an increase in the H + current under symmetrical or asymmetrical pH gradient conditions.